Becoming tobacco‐free: Changes in staff and patient attitudes and incident reports in a large academic mental health and addictions hospital. (17th February 2017) - Riad‐Allen, Lilian; Dermody, Sarah Siodmok; Herman, Yarissa; Bellissimo, Kim; Selby, Peter; George, Tony Peter
Abstract : Background and Objective: Complete tobacco bans in mental health facilities are thought to have the potential for adverse consequences. We evaluated staff and patient attitudes and adverse events associated with implementing Canada's largest, multi‐site academic psychiatric hospital tobacco ban. Methods: A total of 1, 173 staff and 422 patients completed an anonymous attitudes survey at prior to implementation (baseline), and 4–6 months and 10–12 months post‐implementation. The tobacco‐free initiative was implemented in a phased approach, allowing the prospective measurement of changes in attitudes and adverse outcomes such as agitation over a 1‐year period. Results: We observed positive changes in staff and patient attitudes toward the tobacco‐free policy for both staff and patients. Moreover, there was also a statistically significant decrease in patient agitation F (2, 99) = 3.25, p  = .04, but no change F (2, 21) = 1.09, p  = .35 in fire‐related incidents. Discussion and Conclusions: We observed positive changes in staff and patients attitudes and significant decrease in patient agitation during the first year of this tobacco‐free hospital initiative. Scientific Significance: During the first year of this tobacco‐free psychiatric hospital policy, implementation of a tobacco‐free environment in a large mental health and addictions setting was feasible and perceived as desirable by the majority of staff and patients surveyed and a decrease in incidents related to patient agitation was also observed. Further well‐controlled studies with longer study durations are warranted. (Am J Addict 2017;26:183–191)